Pendampingan Proses Pembelajaran Siswa secara Blended Learning dan Pemanfaatan PowerPoint sebagai Media Pembelajaran - Widjojoko Widjojoko; Canti Tresnaratih (Jurnal Pengabdian Masyarakat PGSD, 2022)
Mentoring students while studying is something that is very much needed in covid-19 period because it becomes an effort so that students can achieve their goals in learning. In students’ mentoring, it is also carried out in order to foster self-confidence, have a sense of comfort when learning, grow attitudes and noble behaviors that are creative, innovative and desire to move forward. An effort to achieve learning goals it is not easy so that learning intentions are needed that grow in the child himself, so that children can think well. Young learner, especially at the elementary school level, is where children need concrete objects in every delivery of material given by the teacher. The concrete forms given by the teacher will make it easier for students to reason or imagine something, it can also be something interesting and fun. Through this thematic community service, authors conducted student assistance which was carried out at Ma'rifatul Ulum Islamic Elementary School, Kaliwedi Sub-district, Cirebon, West Java. It is an effort to achieve goals in learning and make PowerPoint media as an alternative for teachers in delivering a material so that the concept of the material being taught can be responded well by students. The assistance for 123 hours through social media platforms is carried out for grade II and V elementary school students The result of this program is that students become motivated to learn during this pandemic after the implementation of blended learning. This assistance is considered very useful in increasing the willingness to learn and can be developed in other forms.